2010
DOI: 10.1088/0954-3899/37/5/055101
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino–nucleus reactions via neutral and charged currents by the quasi-particle random phase approximation (QRPA)

Abstract: We developed the quasi-particle random phase approximation (QRPA) for the neutrino scattering off even-even nuclei via neutral current (NC) and charged current (CC). The QRPA has been successfully applied for the β and ββ decay of relevant nuclei. To describe neutrino scattering, general multipole transitions by weak interactions with a finite momentum transfer are calculated for NC and CC reaction with detailed formalism. Since we consider neutron-proton (np) pairing as well as neutron-neutron (nn) and proton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 54 publications
5
64
0
Order By: Relevance
“…Previous studies have concluded that contributions from the CC reactions are generally larger than those of NC reactions for heavy nuclei [2,[15][16][17].…”
Section: ν-Process Reactionsmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous studies have concluded that contributions from the CC reactions are generally larger than those of NC reactions for heavy nuclei [2,[15][16][17].…”
Section: ν-Process Reactionsmentioning
confidence: 95%
“…Such a small effect in light nuclei is easily understood because the energy gaps between the neutron and proton energy spaces are too large to be effective. However, in intermediate-mass nuclei, such as 56 Fe and 56 Ni, the np pairing effect accounts for 20 ∼ 30 % of the total cross section [16]. Therefore, for the heavy nuclei of interest in the present work, np pairing should be taken into account.…”
Section: Qrpa Frameworkmentioning
confidence: 98%
See 3 more Smart Citations